USAHA KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DAN KARYAWAN - Kiagus Hamzah Kiagus Hamzah (Manajer Pendididikan, 2015)
The objective of this study was compared the school principals efforts in increasing teachers and staff work performance at state junior high school 1 Pendopo and junior high school 1Muara Pinang Empat Lawang, Regency. This research used comparative descriptive method. The subject of this study principal’s, teacher and staff. The data were collected through interview, observations and documentation. Data analysis process included collecting of data, reductioning of data, displaying of data. The results of this research show that the principal’s have done their best. The factors which influenced the school principal’s efforts in increasing the working of teacher’s and staff such as leadership, political will, and renumeration or teacher and staff performanceKey word : Effort, school principal, increase working teacher